2017
DOI: 10.1103/physrevb.95.085107
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structures and excitations in CePd2(Al,Ga)2 series: Development of the “vibron” states

Abstract: CePd 2 Al 2−x Ga x compounds crystallizing in the tetragonal CaBe 2 Ge 2 -type structure (space group P 4/nmm) and undergoing a structural phase transition to an orthorhombic structure (Cmme) at low temperatures were studied by means of neutron scattering. The amplitude-modulated magnetic structure of CePd 2 Al 2 is described by an incommensurate propagation vector k = (δ x , 1 2 + δ y ,0) with δ x = 0.06 and δ y = 0.04. The magnetic moments order antiferromagnetically within the ab planes stacked along the c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
6
14
0
Order By: Relevance
“…For instance, consistent with this mechanism evidence for a VBS in polycrystalline PrNi 2 vanishes as the optical phonon levels shift to lower energies under doping 27 . Putative evidence for vibronic states was also reported in cubic Ce 3 Pt 23 Si 11 28 as well as the tetragonal systems CePd 2 Al 2 10,29 and CeCuAl 3 11 . Moreover, vibronic excitations have even been proposed in rare-earth doped cuprates 30 , as well as geometrically frustrated oxides such as Tb 2 Ti 2 O 7 5,12 and Ho 2 Ti 2 O 7 31 , which underscores the wide-spread relevance.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…For instance, consistent with this mechanism evidence for a VBS in polycrystalline PrNi 2 vanishes as the optical phonon levels shift to lower energies under doping 27 . Putative evidence for vibronic states was also reported in cubic Ce 3 Pt 23 Si 11 28 as well as the tetragonal systems CePd 2 Al 2 10,29 and CeCuAl 3 11 . Moreover, vibronic excitations have even been proposed in rare-earth doped cuprates 30 , as well as geometrically frustrated oxides such as Tb 2 Ti 2 O 7 5,12 and Ho 2 Ti 2 O 7 31 , which underscores the wide-spread relevance.…”
mentioning
confidence: 63%
“…For instance, formation of a vibronic bound state (VBS) between phonons and CEF excitations has been reported in normalCnormalenormalAnormall2 (1922). Similar VBSs have also been proposed to exist in normalPnormalrnormalNnormali2 (23), normalCnormale3normalPnormalt23normalSnormali11 (24), normalCnormalenormalPnormald2normalAnormall2 (13, 25), and normalCnormalenormalCnormalunormalAnormall3 (14) as well as rare-earth doped cuprates (26) and geometrically frustrated oxides (8, 15, 27). However, as the phonon density of states must be large, it is generally believed that the VBS may be formed only with weakly dispersive optical phonons.…”
mentioning
confidence: 63%
“…Monochromatic neutron radiation with a 2.528 Å wavelength, and a multidetector with an angular range of 128 °and a step of 0.1 °between each of the 1280 3 He detection cells, were employed (see e.g. [31,32] for details). The Tm 2 Ir 2 O 7 powder sample was loaded in a cylindrical copper container to ensure good thermal contact, of 6 mm diam and 60 mm height mounted on a dilution insert stick.…”
Section: Experimental Methods and Calculationsmentioning
confidence: 99%
“…[ 75–78 ] Similar VBSs have also been proposed for PrNi 2 , [ 79 ] Ce 3 Pt 23 Si 11 , [ 80 ] and CePd 2 Al 2 . [ 81,82 ] In contrast, an anticrossing, representing a different magneto‐elastic coupling, has been suggested between acoustic phonons and CEF excitations in Pr and PrAl 2 under an applied magnetic field as well as in the magnetically ordered state of VO 4 . While the latter are mediated by dipolar interactions, [ 83–88 ] a generic anticrossing in zero magnetic field that is mediated by quadrupolar interactions may have been observed in PrAlO 3 , [ 89 ] TbVO 4 , [ 90 ] and PrNi 5 .…”
Section: Magneto‐elastic Coupling In Cecualmentioning
confidence: 99%
“…Inspired by studies on CePd 2 Al 2 , neutron spectroscopy in polycrystalline as well as single‐crystal CeCuAl3 revealed a VBS. [ 105–107 ] Considering hybridization with optical phonons, which results in four doublets |normalΓ6,0, |normalΓ6,1, and |normalΓ1,2,0, these studies suggested early on that the symmetry of lattice fluctuations results in a different character of VBSs in a tetragonal environment as compared to cubic systems such as CeAl 2 .…”
Section: Magneto‐elastic Coupling In Cecualmentioning
confidence: 99%